Learning Effectiveness and Level of Motivation Following Educational Technology Learning During Pandemic to State High School Students in Banyuwangi Regency - Fuad Qohar; Anung Priambodo; Achmad Widodo (BIRCU, 2021)
This research generally aims to determine the effectiveness of learning and motivation to participate in high school student learning during the pandemic in physical education subjects. The research was conducted on public high school students in Banyuwangi Regency. In this case, the sample is 1,061 students, divided into 529 students in independent regional schools and 532 students in developed regional schools. This research is a quantitative descriptive study by obtaining data from questionnaires distributed to students. Students who fill out a random questionnaire in two schools that have been selected in the independent region and two schools selected in the developed region. Based on this research data, the learning effectiveness of public high school students in independent areas in Banyuwangi Regency is in the